DIAGNOSIS DAN TATALAKSANA EFUSI PARAPNEUMONIA - Vebiyanti Tentua; Ritha Tahitu (PAMERI, 2022)
Parapneumonic effusion is a pleural effusion associated with bacterial pneumonia, lung abscess or bronchiectasis. The effusion of parapneumonic arising from inflammation in the lung and pleura is due to a direct invasion of bacteria, cascade of inflammatory reactions, and bacterial virulence. The development of the effusion of parapneumonic is grouped into 3 stages: 1) exudative stage, 2) fibrinopurulent stage, 3) organizing stage with pleural peel form. This stage helps categorize effusions into groups to evaluate the risk of cases requiring intervention. Proper management and antibiotic therapy will result in improvements to the effusions of parapneumonic